Behaviour of expansive clay beds with fly ash-stabilised clay cushion. Issue 3 (1st August 2019) - Phanikumar, B. R.
Abstract : Stabilization of expansive soils with various additives such as lime and fly ash has been one of the viable techniques to counteract heave and shrinkage. This paper presents the experimental results obtained from the tests performed on expansive clay beds with fly ash-stabilized clay cushion of varying thickness and fly ash content. The amount and rate of heave, swelling pressure and stress-settlement characteristics of the expansive clay beds were studied. The results indicated that, when fly ash-stabilized clay cushion was provided over expansive clay beds, heave and swelling pressure decreased in comparison to the heave and swelling pressure of untreated expansive clay beds. However, heave and swelling pressure increased with increasing fly ash content for a given thickness of the cushion. But, for a given fly ash content, heave and swelling pressure decreased with increasing thickness. Heave reduced by 70% when 75 mm thick clay cushion stabilized with 10% fly ash content was used. The stress-settlement characteristics of the expansive clay beds with fly ash-stabilized clay cushion improved. The settlement of the footing on a 50 mm thick clay cushion decreased by about 43% when the fly ash content was increased from 0 to 10%.